The Effect of Edamame Jelly on Lowering Blood Pressure in Primary Hypertension Patients - Valensia, Yualeny; Wiboworini, Budiyanti; Hikmayani, Nur Hafidha (JURNAL INFO KESEHATAN, 2024)
Hypertension is the cause of death in Indonesia, with 23.8% of the 1.7 million population. Management of primary hypertension is non-pharmacological therapy carried out by modifying lifestyle, namely increasing consumption of nuts that contain bioactive components that are beneficial for sufferers of primary hypertension, such as edamame (Glycine max (L.) Merrill). This study aims to determine how giving edamame jelly reduces blood pressure in primary hypertension patients. This research was quasi-experimental and used a pre-post-test control group design. The study population consisted of outpatients at the Sumbersari Jember Community Health Center who met the inclusion and exclusion criteria, totaling 42 subjects. Subjects were randomly divided into treatment and control groups. The intervention group was given amlodipine 5 mg/day and edamame jelly 150 grams/day. The control group was only assigned 5 mg of amlodipine. Statistical tests use the Paired t-test, Wilcoxon signed-rank test, and Mann-Whitney U-tests. The test results showed a significant difference in systolic and diastolic blood pressure between the control and treatment groups with a p-value <0.001. The median systolic blood pressure of the control group was 147.5 mmHg, and that of the treatment group was 130 mmHg. The median diastolic blood pressure in the control group was 90 mmHg, and the treatment group's was 80 mmHg. The reduction in systolic blood pressure in the treatment group was 17.5 mmHg greater than in the control group. The decrease in diastolic blood pressure in the treatment group was 10 mmHg greater than in the control group. Giving 150 grams of edamame jelly/day for 30 days effectively reduces blood pressure in sufferers of primary hypertension.